Estados emocionais em professores recém-formados: análise contextual - Reis, Adriano de Lavor [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In general, the early career is a period marked by crises. Hubermam (1992) points out that this period is considered by the teacher as one of life's most difficult professional teaching. According to Machado (2004), the physical education worked only in competitive perspective in school, does not contribute to the school to perform its social role. This approach encourages the use of stigmas, labels and prejudices, so common in school, that marginalize even more students from lower classes, and can make the sport of high performance within the school walls create students with low self-esteem and low motivation within other possible disorders . Thus, this study presents the fundamental importance to aid and support to novice teachers, so that they can understand, and address key emotional aspects that interfere in their practice. Thus, our aim was to identify the most recurrent emotional processes in novice teachers identify and also how these emotional states can influence the professional and personal attitudes of these teachers. Through a bibliographic we seek statements, reports and case studies that provide enough material to our analysis and interpretation in order to collaborate with the study area and proceed to proposals that are not unreasonable or tied to the current system. Among the emotional states reported in the literature, we highlight the main, more present and influent in the beginner teacher as listed as follow: Anxiety, Stress, Fear, Shame, Low Self Confidence and Motivation. Considering these states, Damasio (1996) reports that the United Emotional directly influenced the style and efficiency of cognitive processes, in other words, interfere with the performance of teachers in the teaching front. Thus, Machado (2006) points out that the teacher should have a set of techniques and procedures that drive their practice in a manner appropriate to the leading group. Therefore, the knowledge of Psychology of Physical...

De modo geral, o início da carreira constitui um período marcado por crises. Hubermam (1992) aponta que esse período é considerado pelo professor como um dos mais difíceis da vida profissional docente. Segundo Machado (2004), a educação física trabalhada apenas na perspectiva competitiva na escola, não contribui para que a escola desempenhe seu papel social. Esse tipo de abordagem incentiva o uso de estigmas, rótulos e preconceitos, tão comuns na escola, e que marginalizam, ainda mais, os alunos de classes menos favorecidas, podendo o esporte de “alto rendimento” dentro dos muros da escola criar alunos com baixa auto-estima, motivação dentro outros transtornos possíveis. O estudo apresenta fundamental importância para auxílio e apoio aos docentes iniciantes, de modo que estes possam entender, compreender e enfrentar os principais aspectos emocionais que interferem em sua prática. Desta maneira nosso objetivo foi identificar os processos emocionais mais recorrentes em docentes inexperientes e identificar, ainda, como estes estados emocionais podem influenciar nas atitudes profissionais e pessoais destes professores. Por intermédio de um estudo bibliográfico, então, buscamos depoimentos, relatos e estudos de caso que ofereçam material suficiente para nossa análise e interpretação, de modo a poder colaborar com a área de estudo e avançar para propostas que não sejam descabidas ou atadas ao sistema vigente. Dentre os estados emocionais relatados na literatura, destacam-se como principais, mais presentes e influentes sob o professor iniciante os listados à seguir: Ansiedade; Estresse; Medo; Vergonha; Baixa Autoconfiança e Motivação. Frente a estes estados, Damasio (1996) relata que os Estados Emocionais influem diretamente no estilo e eficiência dos processos cognitivos. Machado (2006) pontua que o professor deve dispor de um conjunto de técnicas e procedimentos que conduza sua prática pedagógica de modo adequado...
Keywords: Esportes - Aspectos psicológicos; Emoções; Professores - Formação; Motivação (Psicologia); Medo; Ansiedade; Stress ocupacional; Professores; Prática profissional